Effect of closed pores on dielectric properties of 0.8Na0.5Bi0.5TiO3-0.2K0.5Bi0.5TiO3 porous ceramics. Issue 7 (July 2018) - Du, Lifei; Du, Xian; Zhang, Li; An, Qunli; Ma, Wanli; Ran, Hongpei; Du, Huiling
Abstract: Porous 0.8Na0.5 Bi0.5 TiO3 -0.2K0.5 Bi0.5 TiO3 ceramics are fabricated via the pore-forming agent method with polymethyl methacrylate (PMMA) and stearic acid (SA) as pore forming agents, and microstructure observations demonstrate that the porosity, pore shape, and pore sizes can be controlled by the synthesis technology. The dielectric properties of porous ceramics are found not only correlated to the pore-matrix composite model, but also have a significant grain-size effect. Based on the Zener Theory, pining forces exerted by pores on the grain boundary are calculated, to explain the shape effect of pores on grain boundary migration. A phase-field simulation is carried out to investigate pore shape effect on the grain size regulation in porous polycrystalline, and simulation results are in good agreements with experiential results as well as theoretical calculations. Thus, a modified equation is proposed to predict the effective permittivity of the porous piezoelectric ceramics by considering effects of porosity, pore shape and grain size.